Studies on Starch Characteristics of Flour Produced from Six Varieties of Musa SPP. Fruits Grown in Southwestern Nigeria - Adebayo, W. A.; Ogunsina, B. S.; Otemuyiwa, I.; Taiwo, K. A. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2025)
This research work investigated starch characteristics of flour produced from six varieties of Musa spp. fruits with the view of promoting its usage as base composition in food development and innovation. There is dearth of information on prediction of glycemic response of different varieties of Musa spp. flour in literatures. This research work therefore investigated glycemic responses of six Musa spp. flour using standard procedures. The descriptive and inferential statistical analysis of measured data was done using Turkey’s post test procedures of GraphPad Prism version 4.00 for Windows. The results showed that the carbohydrate, total starch, slowly digested starch (SDS) and resistant starch (RS) composition of the samples ranged from 90.32 to 93.93%; 473.97 to 488.30mg/g; 33.02 to 36.38% and 21.16 to 27.54, respectively. Furthermore, amylose, amylopectin and predicted glycemic index (pGI) were ranged from 25.10 to 29.02%; 70.93 to 74.90% and 51.11 to 53.31%, respectively. Thus, the results of this study showed that Musa spp. varieties affected glycemic responses of the flour. Therefore, it is concluded that all the six varieties of Musa spp. have low glycemic index and appreciable levels of resistant starch. The data obtained will bridge the information gap for formulation and development of functional foods using Musa spp. flour as a baseline composition.